2016
DOI: 10.3389/fpls.2016.01611
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis TOR Kinase Specifically Regulates the Expression of Nuclear Genes Coding for Plastidic Ribosomal Proteins and the Phosphorylation of the Cytosolic Ribosomal Protein S6

Abstract: Protein translation is an energy consuming process that has to be fine-tuned at both the cell and organism levels to match the availability of resources. The target of rapamycin kinase (TOR) is a key regulator of a large range of biological processes in response to environmental cues. In this study, we have investigated the effects of TOR inactivation on the expression and regulation of Arabidopsis ribosomal proteins at different levels of analysis, namely from transcriptomic to phosphoproteomic. TOR inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 87 publications
7
141
0
4
Order By: Relevance
“…However, how a single protein kinase could act as a master regulator to incorporate various upstream signals to modulate a myriad of cellular activities remains largely unknown. In contrast to recent progress in discovering the downstream effectors of plant TOR signaling [e.g., S6K1, S6K2, E2Fa, E2Fb, RPS6, BZR1, BIN2 (19,22,27,44,45,47)], the upstream regulators of plant TOR signaling remain poorly defined. The small GTPases RHEB and RAG function as the key upstream regulators for mTOR activation in mammalians, but no orthologs of RHEB or RAG GTPases have been identified in plants (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, how a single protein kinase could act as a master regulator to incorporate various upstream signals to modulate a myriad of cellular activities remains largely unknown. In contrast to recent progress in discovering the downstream effectors of plant TOR signaling [e.g., S6K1, S6K2, E2Fa, E2Fb, RPS6, BZR1, BIN2 (19,22,27,44,45,47)], the upstream regulators of plant TOR signaling remain poorly defined. The small GTPases RHEB and RAG function as the key upstream regulators for mTOR activation in mammalians, but no orthologs of RHEB or RAG GTPases have been identified in plants (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies employing TOR kinase inhibitors (rapamycin and AZD8055) have shown leaf chlorosis and yellowing in Arabidopsis (Ren et al, ; Xiong et al, ) suggesting chloroplast damage during TOR kinase inhibition. Recent reports involving TOR inhibitor treatment have indicated that these effects could be due to transcriptional downregulation of genes encoding plastidic ribosomal proteins and photosynthetic proteins as well as those of the tetrapyrrole biosynthesis pathway in Arabidopsis (Dobrenel, Mancera‐Martínez, et al, ; Dong et al, ). Thus, the TORC1 complex has been shown to play a crucial role in biogenesis and maturation of chloroplast to promote leaf and cotyledon greening (Li, Gao, Xue, Wang, & Zhao, ; Li, Song, et al, ; Mohammed et al, ; Sun et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several other potential regulatory factors, including the RNA-binding protein LARP1 (Larelated protein), have been demonstrated to function under TOR control in TOP mRNA regulation (Tcherkezian et al, 2014). In plants, TOP-like motifs are abundant within mRNA 59-UTRs of ribosomal proteins (Dobrenel et al, 2016b), but whether these cis-elements are involved in translation regulation in plants requires further research. Interestingly, several recent publications revealed the existence of so-called R-motifs containing GA, G(A) 3 , G(A) 6 , etc., repeats (Dobrenel et al, 2016;Xu et al, 2017), and provided evidence that the R-motif regulates translation of its mRNA via interaction with poly(A)-binding proteins during immune regulation in plants .…”
Section: -Utr Motifs That Are Controlled By Tor In Animalsmentioning
confidence: 99%
“…Comparative studies of eS6 posttranslational modifications occurring in response to hormones and various abiotic signals documented phosphorylation of several sites within the C-terminal a-helix of eS6 (for review, see Browning and Bailey-Serres, 2015). Recently, phosphoproteomic analysis and western blot with an antibody specifically recognizing phosphorylated Ser-240 has suggested that phosphorylation of Ser-240 is TOR/S6K1 responsive, and, accordingly, TOR inactivation decreases eS6 phosphorylation at this site (Dobrenel et al, 2016b).…”
Section: Ribosomal Protein S6 Is a Major Target Of S6ks Within The Cementioning
confidence: 99%